Severe lactic acidosis and acute leukemia - Loja, David (2004)
We report the case of a 27 year-old patient with acute lymphoblastic leukemia who presented severe lactic acidosis as a metabolic complication. She presented with severe malnutrition, marked anemia and consuming syndrome. There was no reticuloendothelial system compromise and an initial myelogram was normal. These factors delayed the diagnosis and forced the extent of the differential diagnosis. The suspicion of lactic acidosis-associated hematologic neoplasia needed reassessing the case with new myelogram to establish the diagnosis.